DESAIN SISTEM WEB PERSONAL SEBAGAI SARANA PENYAMPAIAN INFORMASI BAGI SIVITAS AKADEMIKA STMIK PPKIA PRADNYA PARAMITA - Marisa, Fitri (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2010)
Personal web made with the development of cyber campus, with the understanding that submission of an online campus information, allowing students to find out what information they needed around campus. It is thus necessary to build Personal Web systems that can be applied for STMIK Pradnya Paramita to provide information from the academic campus. Benefits that can be felt for academicians are able to access academic information, finance, as well as originating from outside the tehubung with the campus. In addition, students and lecturers can set personal web pages in accordance with the actualization of his web site STMIK Pradnya Paramita campus. Â Keywords : Web Personal, STMIK Pradnya Paramita, cyber campus, civitas academica